Growth and yield performance of fodder oats (Avena sativa) grown under different nutrient management practices - KUMAR, DINESH; SINGH, MAGAN; YADAV, M R; MAKARANA, GOVIND; KUSHWAHA, MANISH; DUTTA, SUSANTA; BHATTACHARJEE, S; RAJESH, RAJESH (The Indian Journal of Agricultural Sciences, 2022)
The present experiment was conducted to study residual effect of three maize (Zea mays L.) varieties on oats (Avena sativa L.) (V1: African Tall, V2: J-1006; V3: P-3396) and four nutrient management practices (N0: Control; N1: 100% RDF; N2: 75% RDF + PGPR + Panchagavya spray; N3: 50% RDF + 25% FYM + PGPR + Panchagavya spray) using split plot design. Results showed that residual effect of maize varieties on oats were found to be nonsignificant for different growth attributes and green fodder yield. Nutrient management practices caused significant variations on growth as well as green fodder yield. Significantly better growth in terms of plant height, number of leaves, leaf length, leaf width, stem girth, number of tillers, CGR as well as RGR at both cuts were recorded with application of 75% RDF + PGPR + Panchagavya spray (N2) compared with control (N0) and 100% RDF (N1). The use of 75% RDF + PGPR + Panchagavya spray recorded significantly highest green fodder yield and production efficiency among all nutrient management practices. Our results indicate that integrated use of organic and inorganic nutrient sources (N2) enhances the productivity of fodder oats, besides reducing 25% dose of chemical fertilizers which can sustain the crop productivity.